A systematic review of consumer information search in online and offline environments. Issue 2 (11th April 2021) - C. Haridasan, Anu; Fernando, Angeline Gautami; Saju, B.
Abstract : Purpose: The purpose of this study is to identify major themes and potential research opportunities in online and offline consumer search. Design/methodology/approach: A systematic review was conducted based on 118 articles identified from prevalent journal databases. Keywords frequency analysis was carried out to identify the major themes. An inductive thematic analysis was carried out to verify the generated themes. Findings: Results show that uncertainty, knowledge, perceived risk, price, experience and involvement are the major themes associated with consumer information search. Uncertainty, one of the major themes of offline search, has not been studied in the online search context. Similarly, the previous experience needs to be explored in the context of the offline search. Finally, potential research opportunities for future research has been summarized based on the retrieved themes. Research limitations/implications: The systematic review provides an in-depth understanding on the current research on information search literature with future research directions. Practical implications: This study helps retailers to understand the key elements that motivate consumers to perform external information searches from online and offline sources and to curate targeted information provision strategies to influence purchase decisions. Social implications: Consumers with limited internet availability may access channels prior to decision-making. The themes identified in this study can aid policymakers to design affordable access to these channels. Originality/value: This study adds to the sparse literature on systematic reviews on consumer search for online and offline channels.